Ecological niche modeling and a lack of phylogeographic structure in Vriesea incurvata suggest historically stable areas in the southern Atlantic Forest. Issue 7 (27th June 2019) - Aguiar‐Melo, Camila; Zanella, Camila M.; Goetze, Márcia; Palma‐Silva, Clarisse; Hirsch, Luiza D.; Neves, Beatriz; da Costa, Andrea F.; Bered, Fernanda
Abstract : Premise: Despite the efforts to understand the processes that shape neotropical biodiversity, the complexity of certain biomes, such as the Atlantic Forest (AF), prevents the generalization of patterns. Initially, ecological niche modeling (ENM), with phylogeographic studies, identified past stable areas in the central and northern portions of the AF, while the southern portion was thought to be highly fragmented. Here, we examined the phylogeography, historical patterns, genetic diversity, and population structure of Vriesea incurvata, an endemic species of the southern portion of the AF. Methods: We evaluated 149 individuals using two plastid DNA regions (cpDNA) and 13 nuclear microsatellite markers (nuSSRs) to access the historical patterns, genetic diversity, and structure of V. incurvata populations. We also conducted historical demography and ENM analyses. Results: We found moderate to high genetic diversity and low population structure for both genomes. The cpDNA network revealed high haplotype sharing. The ENM suggested no drastic changes in suitable areas for V. incurvata occurrence, corroborating the finding of no phylogeographic structure. Conclusions: Contrary to some studies, our results indicate that the southern AF was a historically stable climate region for V. incurvata occupation after southward colonization by the species. Past climatic changes probably did not cause structuring among its populations.